Nutritional adequacy in surgical IBD patients. (February 2021) - Fiorindi, Camilla; Dragoni, Gabriele; Alpigiano, Giovanna; Piemonte, Guya; Scaringi, Stefano; Staderini, Fabio; Nannoni, Anita; Ficari, Ferdinando; Giudici, Francesco
Summary: Background & aims: Despite little evidence available to date, the dietary intake assessment is considered a useful tool to optimize dietary intervention for the improvement of the nutritional status of IBD patients. The primary aim was to compare the dietary intake of IBD patients scheduled for surgery with the dietary reference values (DRVs) for the Italian population (LARN) and the ESPEN guidelines for clinical nutrition in IBD. The secondary aim was to describe the dietary patterns of patients with CD and UC in relation to the disease-specific and nutritional parameters and to compare these results to a control group in order to evaluate if similar nutritional intakes than in oncologic patients are found in IBD. Methods: Between January 2019 and March 2020, 62 consecutive IBD patients (46 CD and 16 UC) with age from 18 to 79 years scheduled for surgery were recruited. Patients received a comprehensive nutritional assessment, including food or nutrition-related history, anthropometric and body composition measurements. A group of 61 oncologic patients scheduled for colorectal cancer (CRC) surgery was used as control. Results: IBD patients showed a higher caloric and nutritional intake than CRC group, despite a higher frequency of underweight, and a lower prevalence of overweight and obesity. IBD patients showed an inadequate intake of proteins, n-3 PUFA, fiber, iron, calcium, potassium, magnesium, zinc, vitamin D and vitamin B12 according to ESPEN guidelines for clinical nutrition in IBD and LARN. Oral intake was not influenced by gender, IBD subtype, longer duration of disease and previous surgery. In CD, fistulizing behaviour negatively influenced oral intake. Conclusions: in IBD patients, the evaluation of macronutrients and micronutrients intake before surgery, can contribute to evaluate and to correct the onset of nutritional deficiencies. Specific dietary recommendations seem required, in order to integrate specific nutritional inadequacies. IBD patients referred to surgery have to be considered at high nutritional risk like oncologic patients are.